Supermarket baker's asthma: how accurate is routine health surveillance?. Issue 6 (18th May 2005) - Brant, A; Nightingale, S; Berriman, J; Sharp, C; Welch, J; Newman Taylor, A J; Cullinan, P
Abstract : Background: Regular health surveillance is commonly recommended for workers exposed to occupational antigens but little is known about how effective it is in identifying cases. Aims: To report one large company's surveillance and compare its findings with those of a standard cross-sectional survey in the same workforce. Methods: A supermarket company with 324 in-store bakeries producing bread from raw ingredients conducted a three-stage health surveillance programme in around 3000 bakery employees. The first stage involved the administration of a simple respiratory questionnaire. If chest symptoms were present a second questionnaire focusing on their work relationship was administered. If positive a blood sample was requested for the measurement of specific IgE to flour and fungal α-amylase. The results were compared to an independent cross-sectional survey of employees in 20 of the company's stores. Results: Two hundred and ninety nine (92%) of the company's bakeries took part in surveillance. The overall employee response for the first stage was 77%; a quarter of those with respiratory symptoms reported that they were work related. Seventy four (61%) of those with work related chest symptoms had a measurement of specific IgE to either flour or fungal α-amylase, of whom 30 (41%) had a positive result. Surveillance estimated that 1% of bakery employees (1% bakers, 2% managers, 0.6% confectioners) had work related symptoms with specific IgE. This compared with 4% (7.5% bakers, 3.3% managers, 0% confectioners) in the cross-sectional survey (n = 166, 93% response). Conclusion: Comparison with a standard cross-sectional survey suggests that routine surveillance can underestimate the workplace burden of disease. The reasons may include technical or resource issues and uncertainties over confidentiality or the perceived consequences of participation. More research needs to be done looking into the design and efficacy of surveillance in occupational asthma.